Hubungan fungsi kognitif terhadap e-health literacy pada pasien dengan diabetes militus tipe 2 - Rafikah Safitri; Aini Inayati; Wantonoro Wantonoro (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Type 2 diabetes mellitus (T2DM) has experienced a significant increase globally and is a major health problem. High blood glucose levels in people with T2DM stimulate pro-inflammatory cytokine activity through various biochemical mechanisms within cells, ultimately leading to dysfunction of the blood vessel endothelium. Purpose: To determine the relationship between cognitive function and e-Health literacy in patients with T2DM. Method: This study was condudcted in primary health care in Indonesia using across-sectional design. The study was carried out at jetis community healt canter (puskesmas jetis), Yogyakarta city. The sample was taken by convenience sampling. Results: The mean age of respondents was 68.64 years, with an average duration of diabetes of 5.89 years. Most respondents were female (51.8%) and had completed senior high school education (65.9%). The results showed a significant positive correlation between cognitive function and e-Health literacy (p = 0.001; r = 0.487), indicating a moderate strength of association Conclusion: There is a significant relationship between cognitive function and e-Health literacy in older adults with Type 2 Diabetes Mellitus. Better cognitive function is associated with higher levels of e-Health literacy.   Keywords: Cognitive Function; Diabetes Mellitus; E-Health Literacy.   Pendahuluan: Diabetes mellitus Tipe 2 (DM Tipe 2) mengalami peningkatan yang signifikan secara global dan menjadi salah satu permasalahan kesehatan utama di dunia. Kadar glukosa darah yang tinggi pada penderita Diabetes Melitus akan merangsang aktivitas sitokin proinflamasi melalui berbagai mekanisme biokimia di dalam sel yang pada akhirnya menyebabkan disfungsi pada endotel pembulu darah. Tujuan: Mengetahui Hubungan Fungsi Kognitif terhadap e-Health Literasi Pada Pasien dengan DM Tipe 2. Metode: Penelitian kuantitatif menggunakan desain penelitian cross-sectional yang dilakukan di di wilayah kerja Puskesmas Jetis, Kota Yogyakarta yang berjumlah 85 responden. Variabel penelitian terdiri dari fungsi kognitif dan E-Health Literacy. Analisis data menggunakan analisis univariat dan bivariat menggunakan uji korelasi Spearman Rank. Spearman Rank Hasil: Rerata usia responden adalah 68.64 tahun dengan rerata lama menderita DM selama 5.89 tahun. Sebagian besar responden berjenis kelamin perempuan (51.8%) dan berpendidikan terakhir SMA (65.9%). Hasil uji korelasi menunjukkan terdapat hubungan signifikan antara fungsi kognitif dengan e-Health literacy (p = 0.001; r = 0.487). Nilai korelasi menunjukkan kekuatan hubungan sedang dengan arah positif. Simpulan: Terdapat hubungan yang signifikan antara fungsi kognitif dengan e-Health literacy pada lansia dengan Diabetes Melitu Tipe2.   Kata Kunci: Diabetes Militus; E-Health Literacy; Fungsi Kognirif.